2005
DOI: 10.1152/ajpgi.00334.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased intracellular cAMP on carbachol-stimulated zymogen activation, secretion, and injury in the pancreatic acinar cell

Abstract: A characteristic of acute pancreatitis is the premature activation and retention of enzymes within the pancreatic acinar cell. Because ligands linked to cAMP production may prevent some forms of pancreatitis, we evaluated the effects of increased intracellular cAMP in the rat pancreatic acinar cell. Specifically, this study examined the effects of the cholinergic agonist carbachol and agents that increase cAMP [secretin and 8-bromoadenosine 3',5'-cyclic monophosphate (8-Br-cAMP)] on zymogen activation (trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 20 publications
3
51
0
1
Order By: Relevance
“…Activation of these receptors can cause production of cyclic AMP through adenylate cyclase and this generation of cAMP can initiates or sensitize to pancreatitis responses [26]. Although Alexandre et al [24] detected β-adrenergic receptors in rat acini, NNK mediated zymogen activation was not inhibited when β-adrenergic receptors were blocked.…”
Section: β-Adrenergic Receptorsmentioning
confidence: 99%
“…Activation of these receptors can cause production of cyclic AMP through adenylate cyclase and this generation of cAMP can initiates or sensitize to pancreatitis responses [26]. Although Alexandre et al [24] detected β-adrenergic receptors in rat acini, NNK mediated zymogen activation was not inhibited when β-adrenergic receptors were blocked.…”
Section: β-Adrenergic Receptorsmentioning
confidence: 99%
“…18 In brief, samples were thawed, homogenized, and centrifuged at 1000 g for one minute. To each well of a 24-well Falcon tissue culture plate, the following were added: 100 µl of supernatant and 350 µl of trypsin assay buffer (50 mM Tris [pH 8.1], 150 mM NaCl, 1 mM CaCl 2 , 0.01% BSA).…”
Section: Fluorescent Zymogen Assaymentioning
confidence: 99%
“…18 Amylase secretion into the media was expressed as percent of total amylase (media/[media + cells]).…”
Section: Amylase Secretion Assaymentioning
confidence: 99%
“…Furthermore, systematic review and metaanalyses, which include many of the studies detailed here, find conclusively that current smoking and former smoking are firmly connected with elevated risk for AP (6,126). One singlecenter prospective, cohort study of the natural history of AP, found that smoking was a dosedependent risk factor for recurrent acute pancreatitis (RAP) (18). Furthermore they validated the association of cigarette smoking with CP.…”
Section: Role Of Tobacco In Development Of Pancreatic Disease: Pancrementioning
confidence: 58%
“…Collectively, evidence from these clinical studies supports a dose-dependent association between smoking and chronic pancreatitis; however, a similar association with acute pancreatitis (AP) has also been revealed (18,108,126). In a Danish study with a mean follow-up of 20.2 years, a link between smoking and increased risk of AP was observed, independent of alcohol consumption.…”
Section: Role Of Tobacco In Development Of Pancreatic Disease: Pancrementioning
confidence: 89%